1-Desamino-8-D-Arginine Vasopressin (DDAVP) Infusion in Type IIB von Willebrand’s Disease: Shortening of Bleeding Time and Induction of a Variable Pseudothrombocytopenia - Casonato, Alessandra; Teresa Sartori, M; de Marco, Luigi; Girolami, Antonio (Thrombosis and Haemostasis, 1990)
We have investigated the effects of 1-desamino-8-D-arginine vasopressin (DDAVP) infusion on platelet count and bleeding time in 4 patients with type IIB von Willebrand’s disease (vWd). Three of four patients showed a normalization of the bleeding time within 1 h after the infusion, while bleeding time was not modified in the fourth. In accordance with the literature, thrombocytopenia was observed after DDAVP infusion, but this thrombocytopenia was due to the anticoagulants used for blood collection. In two patients (F. I., G. F.) no thrombocytopenia was observed when platelets were counted by fingerstick method but there was a 20% platelet decrease in blood samples collected in sodium citrate and a 50% decrease in samples collected in EDTA. Dramatic falls in platelet counts (70–95%) were observed in the additional two patients (C. A., D.Z.) after DDAVP infusion, when both sodium citrate or EDTA were used as anticoagulants. In the latter two patients there was also a 50% decrease in platelet count when the fingerstick method was used. The decrease in the patient’s platelet count in EDTA samples after DDAVP infusion could be prevented, in part, by the previous additions of an anti GPIb monoclonal antibody and an anti GPIIb-IIIa monoclonal antibody.Thus, the thrombocytopenia observed in the four IIB vWd patients studied after DDAVP infusion seems to be, at least partially, a pseudothrombocytopenia depending on the calcium concentration in the blood samples and the availability of GPIb and GPIIb-IIIa receptors. These findings and the normalization of the bleeding time observed in three of the four patients has led us to reconsider the possible use of DDAVP in the treatment of our IIB vWd patients.